Research on the impact of toxic gases around the Kharakhorum museum (Mongolian Journal of Arts and Culture, 2025)
In recent years, the study of toxic gas pollution has been widely used in the museum sector, where valuable cultural heritage is preserved. This type of study was developed by Japanese scientists, who conducted a variety of studies on air pollution and organic acids in the environment and analyzed how they negatively affect monuments. The factors that contribute to the deterioration of monuments include cement in construction, plywood, glue and other materials used to make museum halls and exhibition enclosures, as well as visitors. Identifying and measuring these toxic gases that affect the museum environment, and taking measures in case of high pollution are among the problems facing museums. The toxic gases that are most commonly produced and affected in museums are formaldehyde, ammonia, and organic acids. In order to clarify the causes of these acids, Kharkhorum, for the first time in Mongolia, collaborated with the Kitagawa Group of Japan and the National Center for Cultural Heritage of Mongolia to conduct environmental pollution studies in the museum’s exhibition halls, treasury, and outdoor areas in 2018 and 2024. Using general cognitive methods of analysis, synthesis, comparison, and comparison, combined with measurement, experiment, observation, and graphic methods, the environmental pollution of the Kharkhorum Museum was determined and pollution was reduced by placing Japanese filter paper that absorbs toxic gas acids on glass box.Хархорум музейн орчинд явуулсан хорт хийн нөлөөллийн судалгааХураангуй: Музейн үзмэр нь он удаан жилийн турш хадгалагдан бидний үр хойчдоо өвлүүлэн уламжлан үлдээх соёлын чухал үнэт өв юм. Хархорум музей 2018 оноос эхлэн соёлын үнэт өвийн хадгалалт, хамгаалалт, үндсэн хэв шинж чанарыг алдагдуулахгүй байх, насжилтыг уртасгах зорилгын хүрээнд Япон улсын хүрээлэн буй орчны судалгааны төв, Китагава групптэй хамтран музейд тогтвортой орчин бүрдүүлэх, шилэн хоргон дахь үзмэрт нөлөөлж буй хорт хийг олж тогтоох, хүрээлэн буй орчны бохирдлын судалгааг явуулж эхэлсэн. Энэхүү өгүүлэлд формальдегид, аммиак, органик гэсэн гурван хүчлийн тухай үндсэн ойлголт, 2018, 2024 онуудад тус музейн үзэсгэлэнгийн танхимын шилэн хоргон дахь үзмэрт муугаар нөлөөлж буй хүчин зүйл, хорт хий үүсэж буй шалтгааныг олж тогтоосон үр дүнгээс танилцуулж байна. Танин мэдэхүйн ерөнхий арга задлан шинжлэх, нэгтгэн дүгнэх, харьцуулан жиших аргыг хэмжилт, туршилт, ажиглалт, графикийн аргуудтай хослуулан хэрэглэж, Хархорум музейн орчны бохирдлыг тодорхойлон, Япон улсын хорт хийн хүчлийг сорогч филтер цаасыг шилэн хоргонуудад дэвсэж бохирдлыг бууруулав.Түлхүүр үгс: музей, хадгалалт хамгаалалт, туршилт, хорт хий